Relationship between Learning Style and Interest in Learning with Social Studies Learning Outcomes for Grade IV - Yunita, Ela; sumilah, sumilah (Elementary School Teacher, 2021)
The purpose of this research was to examine the correlation between learning styles and learning interest toward socialstudies learning outcomes of the fourth grade students at elementary school of Kartini Cluster, Pati Regency. The type ofthis research is a correlation study. The population in this research were the fourth grade students of elementary schoolof Kartini Cluster, Pati Regency and consisted of 121 students. The sampling technique used Saturated Sampling. Datacollection techniques used questionnaries, documentation, and interviews. The instrument test was standardized by usingvalidity and reliability tests. The prerequisite analysis test used the normality, linearity, and multicollinearity tests. Whilethe data analysis technique used descriptive statistics, Product Moment correlation analysis, multiple correlation analysis,significant test, simple linear regression analysis, multiple regression analysis. The results showed that there was apositive and significant correlation between learning styles and learning interest together toward social studies outcomesthat proved by its score was 0.631 and the value of table data= 0.176. The contribution of learning styles and learninginterest variables on social studies learning outcomes was 62.8% included in the strong category.Keywords: learning style; learning outcomes; interest to learn